Integrating a holistic health care setting centered around the traditional healing practices of the ethnolinguistic groups of Davao City - Intong, Rey Justine D. (2020)
This thesis was conducted to help alleviate the need for health infrastructure in Indigenous communities in Davao City by establishing a general set of guidelines for holistic health care settings through the lens and integration of the Holistic Health philosophy with traditional ethnolinguistic healing practices. The researcher conducted interviews and Focus Group Discussions (FGDs) with three Indigenous tribes present within the Davao city area as well as documenting their present and traditional use of spaces. Interviews with holistic and bio-medical health professionals were also conducted so as to find commonalities and insights for health care spaces. The study found that traditional ethnolinguistic healing practices typically involve home spaces such as the kitchen, living room, and bed room, and locally found herbs and various plan based treatments. Religious prayers and rituals are also used when necessary. Specific tools and items used range from typical apparatus such as cups, knives, and pots, to culture specific equipment such as traditional machetes or ornamentation. The Guidelines established in this study center around the use the traditional kitchen and fireplace or abohan which is the most used area in preparation of healing treatments, and the designing of adaptive spaces for versatility. Other spaces such as a Panubaran or religious ritual areas should also be present. There should also be an emphasis on situating the proposed development in near proximity to Indigenous communities, as well as a focus on maintaining a connection with the natural environment.